Ekstrakurikuler Permainan Sepak Takraw di Tiga Jenjang Sekolah - Dhika Bayu Mahardhika; Andika Nurdiansyah; Hanifa Nur Hasanah (Lembaga Pengembangan Kinerja Dosen, 2025)
Sepak takraw is a traditional sport originating from Southeast Asia and is very popular in countries such as Malaysia, Thailand, and Indonesia. The main objective of this study is to conduct a literature analysis on sepak takraw extracurricular activities held at various levels of schools. This study was conducted by 4th semester students of class B of the Physical Education, Health and Recreation Study Program, Faculty of Teacher Training and Education, class of 2023. The results of observations in 80 schools spread across the areas of Jakarta, Bekasi, Cikarang, Karawang, and Purwakarta revealed that the existence of sepak takraw as part of extracurricular activities and physical education learning materials is still very limited. This finding shows the lack of attention to this traditional sport in the educational environment, so systematic efforts are needed to introduce, develop, and integrate sepak takraw into physical education programs in schools. This study uses a qualitative method because the data collected and analyzed are non-numerical, such as interviews, observations, and field texts. The purpose of this study is to conduct a literature analysis on sepak takraw extracurricular activities held in schools at each level.